Levator Aponeurosis and Muller Muscle Plication Reinforced With Levator Sheath Advancement for Blepharoptosis Correction. Issue 7 (October 2017) - Byun, Jin Suk; Hwang, Kun; Lee, Sang Yun; Kim, Hak Tae; Kim, Kenneth
Abstract : Abstract: The authors innovated the levator aponeurosis and Muller muscle plication reinforced with levator sheath advancement (AMPSA) for blepharoptosis correction. The orbital septum was opened 1 mm above its fusion with the levator aponeurosis. The preaponeurotic fat was retracted and the thickened part of the levator sheath was identified. Two plication sutures were made: medial suture at the medial border of the pupil and lateral between the lateral border of the pupil and the lateral limbus. A needle with 6-0 nylon thread first bit the tarsal plate approximately 1 mm below its upper border, then bit the levator aponeurosis and the Muller muscle together at 3 to 6 mm above the upper border of the tarsal plate. The needle bit 1 to 3 mm of the thickened part of the levator sheath and the suture was tied. A total of 116 eyes were operated on using levator aponeurosis and Muller muscle plication (AMP), and 79 eyes using AMPSA. The mean follow-up period was 11.4 months. In the AMP group, the postoperative marginal reflex distance-1 (MRD-1) (3.8 ± 0.2 mm) was significantly greater than the preoperative MRD-1 (2.7 ± 0.3 mm) ( P < 0.001). In the AMPSA group, the postoperative MRD-1 (3.5 ± 0.3 mm) was also significantly greater than the preoperative MRD-1 (1.7 ± 0.4 mm) ( P < 0.001). The improvement in MRD-1 was greater in the AMPSA group (1.7 ± 0.4 mm) than in the AMP group (1.1 ± 0.3 mm) ( P < 0.001). The difference in the MRD-1 outcome between AMPSA and AMP (0.6 mm) was obtained by advancing the thickened part of the levator sheath. AMPSA may be an effective procedure for correcting blepharoptosis.